Geospatial analysis of the associations between environmental contamination with livestock feces and children with chronic fascioliasis in the Anta province of Cusco, Peru. - Melinda Barbara Tanabe; John Prochaska; Maria Luisa Morales; Martha Lopez; Benicia Baca-Turpo; Eulogia Arque; Miguel Mauricio Cabada (Public Library of Science (PLoS), 2022)
Fasciola hepatica is a neglected parasitic infection with significant human health and livestock industry impact. The Andean Altiplano harbors an estimated 50% of the Fasciola's world infection burden. There is scarce data regarding the spatial associations between different Fasciola hosts. In this project, we aimed to determine the geospatial relationships between Fasciola eggs passed in feces of different livestock species and the risk of infection among each household as a unit. We used data from a cross-sectional study evaluating children and livestock feces for Fasciola infection around households in three districts of Anta province, in the Cusco region of Peru. Each sample was geographically tagged and evaluated for fascioliasis using microscopy methods. A total of 2070 households were included, the median age was 9.1 years (6.7-11.8), 49.5% were female, and 7.2% of the households had at least one infected child. A total of 2420 livestock feces samples were evaluated. The infection rate in livestock samples was 30.9%. The highest infection rate was found in sheep with 40.8%, followed by cattle (33.8%), and swine (26.4%). The median distance between a household with an infected child to a positive animal sample was 44.6 meters (IQR 14.7-112.8) and the distance between a household with no infected children to a positive animal sample was 62.2 meters (IQR 18.3-158.6) (p = 0.025). The multivariable logistic regression adjusted by presence of poor sanitation, unsafe water consumption, altitude, and presence of multiple infected children per household demonstrated an association between household infection and any cattle feces at a 50 meters radius (Uninfected: OR 1.42 (95%CI 1.07-1.89), p = 0.017. Infected: OR 1.89 (95%CI 1.31-2.73), p = 0.001), positive cattle feces at a 100 meters radius (OR 1.35 (95% CI 1.08-1.69), p = 0.008), and negative cattle feces at a 200 meters radius (OR 1.08 (95% CI 1.01-1.15), p = 0.022). We identified potential hot and cold spots for fascioliasis in the Anta province. An association between environmental contamination with feces from different livestock species and infected children in rural households was found in our study. Local health authorities may apply this strategy to estimate the risk of infection in human populations and apply targeted interventions.